Queerowa historia. Doświadczenie obozu jenieckiego w perspektywie osób queer w dramacie Julii Holewińskiej "Katyń. Teoria barw" - Żyła, Weronika (Zagadnienia Rodzajów Literackich, 2024)
In this work, the author undertakes a comprehensive analysis of the drama Katyń. Teoria barw [The drama of Katyń. The theory of colors] by Julia Holewińska within the framework of queer theory. The study addresses the significance of this exploration, emphasising the limited representation of non-normative groups in historical narratives, a consequence of the specific political trajectory adapted by the then government. The article posits that artistic expressions, such as films, books, or performances, can be construed as counter-hegemonic interventions within the realm of the arts. In this regard, the artistic domain stands out as a unique space where marginalised histories find a platform for development. The Katyn massacre is a poignant symbol within Polish memory policies, and Katyń. Teoria barw disrupts the official narrative surrounding this historical event by incorporating the experiences of queer persons and women into the storyline. The theoretical underpinnings of this research encompass concepts related to counter-memory, the performance of history, queer theory, and its influence on altering historical narratives, along with the application of Chantal Mouffe’s agonistic model of democracy. The analysis of the drama reveals the potential for constructing a counter-historical narrative, characterising it as an endeavour that challenges the hegemony of the system by reclaiming aspects of Polish history through artistic activities. Holewińska’s narrative is presented as a paradigm of counter-hegemonic artistic practice, employing tools that subvert hegemony. These tools include the deconstruction of the dominant heterosexual and masculine fiction through the introduction of a counter-historical narrative portraying the homosexual camp experience, and the representation of the body using categories described by Ewa Domańska as “necros.”